Best Practices for Highway Project Owners in Enhancing Construction Project Management - Xu, Bo (Journal of Global Economy, Business and Finance, 2026)
In recent years, the rapid expansion of highway infrastructure projects has significantly advanced the domestic highway transportation system. Concurrently, public scrutiny regarding the construction quality of highway projects has intensified. In response, highway project owners are required to prioritize and systematically enhance construction project management practices. This entails rigorous supervision and oversight of on-site implementation, timely identification of issues arising during the construction management process, and the adoption of appropriate corrective actions followed by thorough outcome inspections. These measures collectively contribute to the continuous improvement and further development of highway project execution.